Development and Validation of a Web-Based Thesis Title Submission Information System Using the ADDIE Model at Indonesian Maritime Polytechnic - Endang Lestari; Masrupah; Wardimansyah Ridwan; Muhammad Hidayat L (Information Technology Education Journal, 2026)
Purpose – This study aimed to develop and validate a web-based thesis title submission information system for Merchant Marine Polytechnic of Makassar and to examine cadets' user acceptance of the system. Design/methods/approach – This research employed a research and development design using the ADDIE through observation, documentation, expert-validation questionnaires, user-acceptance questionnaires, and supporting interviews. Data were analyzed descriptively using mean scores, percentages, and an aggregate Aiken-type validity index because only aspect-level validation data were available. Findings – Expert validation showed very high feasibility: information system introduction (M = 4.63; AVI = 0.91), user control (M = 4.83; AVI = 0.96), system interface (M = 4.50; AVI = 0.88), and final system performance (M = 4.50; AVI = 0.88). The small-group trial obtained M = 4.36 (87.27%), indicating a very practical system. The field trial showed positive user acceptance in ease of use (M = 4.22; 84.40%) and interface quality (M = 4.16; 83.20%). Research implications/limitations – The system can potentially support more efficient and better documented thesis title submission services. However, the evaluation was limited to one maritime polytechnic, did not include objective operational comparison with the manual workflow, and could not report reliability or dispersion statistics because item-level data were unavailable. Originality/value – This study contributes a documented ADDIE-based development and validation process for a multi-role academic administration system in a maritime higher education context, covering cadet submission, supervisor review, program-head validation, status tracking, and controlled institutional piloting readiness.